Subtemporal approach for treatment of basilar bifurcation aneurysms (with report of 3 cases) - Wen⁃zhe JIN; Huan⁃yu WANG; Hong WANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2012)
The study was to explore the operative experience in 3 patients with basilar bifurcation aneurysms treated with microsurgery via subtemporal approach. The clinical manifestations, angiograms, and surgical operation were retrospectively analyzed. The effect of clipping treatment was satisfactory in 2 patients. One case was treated with remnant neck of aneurysms in order to protect perforating branches of artery. The blood flow was unobstructed in parent artery and distal artery. Patients were followed for 6 months to 2 years after surgery. The recovery was good. The patients' mRS (modified Rankin Scale) were 2, 0, 1, respectively. Barthel index [Activities of Daily Living (ADL)] were 65, 100, 95, respectively. There⁃fore the subtemporal approach is safe and effective in the treatment of basilar bifurcation aneurysm surgery.